أحكام الملكية والالتزام والصيانة في الإجارة المنتهية بالتمليك: دراسة تحليلية في المصارف الإسلامية الماليزية واقتراح تطبيقها في المصارف الأفغانية - عبد الحميد، بخت الرحمن عثماني (Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2018)
The study focused on the Ruling of Ownership, Commitments and Maintenance in al-Ijarah al-Muntahiyyah Bittamlik. It is an analytical study of the Shari'ah rulings of the contract applied in Maybank Islamic and Bank Mu'amalat Malaysia Berhad together with an attempt of feasibility in the implementation of the contract in Afghan National Bank and New Kabul Bank. The analysis of the rulings in such contract is carried out in three stages: firstly, the rulings are presented in the light of Islamic jurisprudence, secondly, they are presented in the light of Malaysia Hire-Purchase Law “Hire-Purchase Act 1967”, and also presented in the light of the applied contract in Malaysian Islamic banks, and thirdly, these rulings are presented in the light of Afghan Civil Law and Afghanistan Central Bank's law together with the possibility of implementation of the contract in Afghan National Bank and New Kabul Bank in the light of the practical experiences of the Malaysian Islamic banks and Afghan civil law. The purpose of this study is not to highlight the concepts of the rulings regarding this contract, but to discover the means and the ways of operation of al-Ijarah al-Muntahiyyah Bittamlik in Malaysian Islamic banks and to analyze the concepts of ownership, commitment and maintenance in such contract in order to find out the compatibility between the theoretical and practical implementations of the AITAB facility in the selected banks. The aim of this study is also to find out the extent of potential implementation of AITAB facility in the selected Afghan banks in the light of the Afghan civil law. The study concluded that the Malaysian Islamic banks in the implementation of al-Ijarah al-Muntahiyyah Bittamlik refers to the Malaysian Hire-Purchase Law "Hire-Purchase Act 1967" and the study also concluded that there is a possibility of applying the contract in Afghan banks in the light of the practical experiences of Malaysian Islamic banks. The study found that the difference between the practical experiences of Malaysian Islamic banks and between the Afghan civil law and Afghanistan Central Bank's law regarding the operation of this contract in Afghan banks are not contradictory. The research concluded that Afghanistan is in urgent need to have a legal and clear legislative framework in the area of Islamic Banking and finance, especially in the field of al-Ijarah al-Muntahiyyah Bittamlik based on multi financial institution and company levels through conducting conferences and researches as well as publishing scientific articles related to Islamic banking products. The study also concluded that the said country is in need to learn from Malaysian Islamic Financial Services Act and its Islamic banking finance and Takaful experiences.